Beneficial effects of natural compounds on experimental liver ischemia-reperfusion injury. Issue 9 (31st March 2021) - Dossi, Camila G.; Vargas, Romina G.; Valenzuela, Rodrigo; Videla, Luis A.
Abstract : Liver ischemia-reperfusion injury severely compromises the organ functionality, whose underlying mechanisms involve cellular and molecular interrelated processes leading to the development of an excessive inflammatory response. Abstract : Liver ischemia-reperfusion injury (IRI) is a phenomenon inherent to hepatic surgery that severely compromises the organ functionality, whose underlying mechanisms involve cellular and molecular interrelated processes leading to the development of an excessive inflammatory response. Liver resident cells and those recruited in response to injury generate pro-inflammatory signals such as reactive oxygen species, cytokines, chemokines, proteases and lipid mediators that contribute to hepatocellular necrosis and apoptosis. Besides, dying hepatocytes release damage-associated molecular patterns that actívate inflammasomes to further stimulate inflammatory responses leading to massive cell death. Since liver IRI is a complication of hepatic surgery in man, extensive preclinical studies have assessed potential protective strategies, including the supplementation with natural compounds, with the objective to downregulate nuclear factor-κB functioning, the main effector of inflammatory responses. This can be accomplished by either the activation of peroxisome proliferator-activated receptor-α, G protein-coupled receptor 120 or antioxidant signaling pathways, the synthesis of specific pro-resolving mediators, downregulation of Toll-like receptor 4 activity or additional contributory mechanisms that are beginning to be understood. The latter aspect is a crucial issue to be accomplished in preclinical studies, in order to establish adequate conditions for the supplementation with natural products before major liver surgeries in man involving warm IR, such as hepatic trauma or resection of large intrahepatic tumors.